Identification of Bacterial Isolates and Their Antimicrobial Susceptibility Pattern from Wound/Pus Sample in a Tertiary Care Hospital, Gwalior, India - Rajput, Kamini; Johri, Sonia; Goyal, Anju (Annals of the National Academy of Medical Sciences (India), 2023)
Objective The goal of this investigation was to look at the frequency and dispersal of bacteria isolated from pus/wound, as well as their susceptibility patterns.Materials and Methods A study was conducted on 175 patients who provided pus and/or wound discharge samples in different wards (outpatient department or inpatient department). MacConkey agar and blood agar plates were immediately inoculated with samples and incubated at 37°C for 24 hours. The Gram stain and biochemical tests were used to identify all isolates after incubation. Kirby–Bauer's disc diffusion method was used to perform sensitivity tests on Mueller–Hinton agar plates.Results This study covered 175 patients, with a bacterial isolation rate of 102 (58.28%). Males outnumbered females in the samples (M:F = 1.8:1), with a median age of 45 years as majority were in the age group of 40 to 60 years which was 41 (40.20%). Total 90.1% samples showed monomicrobial infection, whereas 9.8% showed polymicrobial infection, and total 112 bacterial strains were isolated.Conclusion Escherichia coli was the most prevalent isolate in present investigation, followed by Pseudomonas aeruginosa. Chloramphenicol is the only antibiotic which is effective for both gram-negative bacilli and gram-positive cocci. This report's susceptibility statistic may be worth considering for developing empiric treatment regimens for pyogenic infections.
Keywords: pus sample; wound infection; antimicrobial susceptibility; pyogenic; multidrug resistant; GNB; GPC